Preservation and interpretation of pollen in hyaena coprolites: taphonomic observations from Spain and southern Africa - Scott, Louis; Fernandez-Jalvo, Yolanda; Carrion, Jose; Brink, James (Bernard Price Institute for Palaeontological Research, 2003)
A survey of palynological research on hyaena coprolites from 10 fossil sites in southern Africa and 4 from Spain shows that coprolites from 10 out of the 14 sites contained fossil pollen. Pollen-bearing coprolites are generally richer in pollen than the surrounding sediments. Provisionally it seems that the sites with poor or no pollen in coprolites are relatively old or have been exposed to wet and dry moisture fluctuations, namely Makapansgat, Gran Dolina, Redcliff Cave and Erfkroon. This suggests that conditions during their long histories eventually destroyed pollen through oxidation associated with regular saturation of sediments. The composition of pollen spectra and preservation of pollen grains from coprolites is compared with that in fresh hyaena dung. SEM studies suggest that pollen grains in fresh dung and in fossil coprolites if preserved under suitable cave conditions, are generally well preserved with little damage. The damage traits require further systematic investigation in order to assess their taphonomic significance but selective destruction of pollen through ingestion, if any, seems to be light. Of particular interest to palaeoenvironmental studies is the observation that pollen assemblages preserved in hyaena dung are likely to provide relatively unbiased characterizations of vegetation representative of the wide surroundings in which the hyaenas were active. This implies that where pollen was relatively wellpreserved in coprolites, it can provide palaeoenvironmental information extending beyond the immediate environs of the site in which they were found. Any possible bias introduced through behaviour-related pollen trapping is, however, difficult to exclude.
Main article
Keywords: palynology, hyaena coprolites, taphonomy, South Africa, Spain.